Numerical simulation of laser-supported combustion wave induced by millisecond-pulsed laser on aluminum alloy. (23rd November 2015) - Zhang, W; Wei, Z; Wang, Y B; Jin, G Y
Abstract: In this paper, the energy transmission of a laser-supported combustion wave (LSCW) is numerically studied, which includes inverse bremsstrahlung, thermal conduction and convection. A physical model is established to simulate an LSCW induced by millisecond-pulsed laser on aluminum alloy. This physical model is a 2D axis-symmetric numerical model of radiation gas dynamics. Moreover, the simulation focuses on the interaction process in different laser conditions such as various pulse widths and peak energies. As a result, the speed of the LSCW increases by increasing the laser energy while keeping the laser pulse constant, whereas the speed is reduced by increasing the laser pulse width while keeping the laser energy constant. After a comparison of the theoretical, numerical and experimental results, analyses are performed while the experimental results are explained reasonably. Furthermore, the consistency between the numerical and experimental results implies that the numerical calculation model used in this paper can describe the motion of the LSCW of the millisecond-pulsed laser on aluminum alloy very well.